The role of communication activities in Saudi sports clubs in rejecting sports fanaticism 2025 (The International Journal of Educational Sciences and Arts, 2025)
This research aims to examine the role of communication activities organized by Saudi sports clubs in reducing sports fanaticism. This research analyzes the impact of these activities on fans' awareness and behavior, and evaluates their success in achieving their goals. It also seeks to provide proposals for developing sports communication strategies that contribute to creating a more positive sports environment. The research relies on a field study based on the opinions of fans, media professionals, and those responsible for communication activities in sports clubs, in addition to an analysis of previously implemented initiatives in this field. This study highlights the importance of adopting effective and innovative communication strategies to combat sports fanaticism and calls for enhanced cooperation between sports clubs and relevant authorities to achieve the desired goals. Sports are not simply competition between teams; rather, they are a means of promoting positive values ​​and building a cohesive society based on mutual respect and appreciation.
Keywords: Communication Activities; Sports Clubs; Saudi Arabia; Sports Fanaticism